Knowledge, Attitudes and Behavior of Female Students in Breast Self-Examination - fatmawati Ibrahim; Eka Rati Astuti; Nurhidayah Nurhidayah; Nurfaizah Alza (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
Breast Self-Examination (BSE) is a simple, effective, and independently performed method for early detection of breast cancer. This study aims to determine the level of knowledge, attitudes, and behavior of female students regarding BSE implementation and to analyze the relationship between knowledge and attitudes with behavior. This study is a quantitative study with a descriptive analytical approach and a cross-sectional design. The sample consisted of 129 second-semester female students of the D-III Midwifery Study Program at the Gorontalo Ministry of Health Polytechnic, selected by total sampling. The results showed that most respondents had good knowledge (65.9%), very good attitudes (57.4%), and supportive behavior in performing BSE (87.6%). The results of the ANOVA test showed a significant relationship between knowledge (p = 0.017) and attitudes (p = 0.009) with BSE behavior. It can be concluded that the better the knowledge and attitudes of female students, the more likely they are to have behaviors that support the independent implementation of BSE. Therefore, continuous health education interventions are needed to improve students' understanding and motivation in performing BSE regularly.